2,2 `-(Disulfanediyl)dibenzoic acid-N,N `-bis(3-pyridylmethyl)ethanediamide (1/1) - Arman, H.D.; Miller, T.; Poplaukhin, P.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title cocrystal, C(14)H(14)N(4)O(2)center dot C(14)H(10)O(4)S(2), comprises a twisted 2,2'-(disulfanediyl)dibenzoic acid molecule [dihedral angle between the benzene rings = 76.35 (10)degrees] and a U-shaped N,N'-bis(3-pyridylmethyl)ethanediamide molecule with the pyridyl groups lying to the same side of the central diamide moiety [C-C-C-N = 113.8 (2) and -117.6 (2)degrees]. The latter aggregate into supramolecular tapes propagating along the a axis via centrosymmetric eight-membered amide {center dot center dot center dot OCNH}(2) synthons. Intramolecular N-H center dot center dot center dot O hydrogen bonds are observed. The 2,2'-(disulfanediyl)dibenzoic acid molecules form carboxyl-pyridine O-H center dot center dot center dot N hydrogen bonds, bridging a pyridine residue below the plane of the tape and one above the plane with two intervening N,N'-bis(3-pyridylmethyl) ethanediamide molecules. The supramolecular chains are consolidated in the crystal packing by C-H center dot center dot center dot O contacts. An intermolecular C-H center dot center dot center dot S interaction also occurs.